1998
DOI: 10.1007/s004280050179
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous nerves in atopic dermatitis

Abstract: Although pruritus is the cardinal symptom of atopic dermatitis, its mechanism is not well understood. Free nerve endings in the skin are involved in pruritus as itching receptors. We studied the cutaneous nerve fibres in lichenified lesions of 16 patients with adult atopic dermatitis. On immunohistochemistry, fibres immunoreactive for neurofilament, neuron-specific enolase, and protein gene product 9.5 were observed in the papillary dermis and dermoepidermal junctions as well as in the epidermis. In these area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(28 citation statements)
references
References 16 publications
0
28
0
Order By: Relevance
“…Dermatological conditions in theory could affect epidermal innervation, increasing or decreasing its density (Misery et al , 2014). Indeed, histological observations have indicated that epidermal nerve fibres are present at higher densities in the skin of patients with itchy psoriasis (Nakamura et al , 2003; Taneda et al , 2011), lichenified atopic skin (Urashima and Mihara, 1998), photodamaged skin (Toyoda et al , 2005) and in a mouse model of xerosis (Tominaga et al , 2007), than in healthy individuals. On the other hand, IENFD have been shown to be reduced in conditions such as sensitive skin (Buhé et al , 2016), prurigo nodularis (Schuhknecht et al , 2011), and in a case report of grafted skin (Zeidler et al , 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Dermatological conditions in theory could affect epidermal innervation, increasing or decreasing its density (Misery et al , 2014). Indeed, histological observations have indicated that epidermal nerve fibres are present at higher densities in the skin of patients with itchy psoriasis (Nakamura et al , 2003; Taneda et al , 2011), lichenified atopic skin (Urashima and Mihara, 1998), photodamaged skin (Toyoda et al , 2005) and in a mouse model of xerosis (Tominaga et al , 2007), than in healthy individuals. On the other hand, IENFD have been shown to be reduced in conditions such as sensitive skin (Buhé et al , 2016), prurigo nodularis (Schuhknecht et al , 2011), and in a case report of grafted skin (Zeidler et al , 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In preliminary experiments, we found that there were many nerve fibers in the thickened epidermis, although in the superficial layers of normal skin, nerve fibers were mainly distributed in the dermal region close to the epidermis (T. Miyamoto et al, unpublished observation). The increased distribution of nerve fibers in the thickened epidermis is also apparent in patients with pruritic disease such as atopic dermatitis and chronic renal failure (38,39). Thus, although further studies are needed, it is possible that increase in nerve fibers in the epidermis is at least partly involved in the AEW-induced spontaneous scratching.…”
Section: Discussionmentioning
confidence: 99%
“…In human atopic dermatitis, scratching the itchy sites was thought to induce serious dermatitis, and it frequently caused hypertrophy of peripheral nerve and hyperplasia of neural fiber bundles (22)(23)(24), leading to a high density of peripheral nerve fibers along with the progress of the disease. This bad cycle might be one of the bases for the refractory atopic skin inflammation (25).…”
Section: Discussionmentioning
confidence: 99%